Produção de bovinos de corte em pastagem de aveia preta e azevém submetida à adubação nitrogenada - Lupatini, Gelci Carlos [UNESP]; Restle, João; Vaz, Ricardo Zambarda; Valente, Alexandre Vargas; Roso, Cledson; Vaz, Fabiano Nunes (FapUNIFESP (SciELO), 2013)
We evaluated animal production on black oats (Avena strigosa Schreb.) and italian ryegrass (Lolium multiflorum) pasture submitted to nitrogen top fertilization of 0; 150 and 300 kg ha-1, in the form of urea. We used 36 calves with average age and average weight of 10.5 months and 180 kg, respectively, as test-animals. The grazing system used was continuous with variable stocking rate. The block design was completely randomized with three replicates (paddock). Average weight gain was similar for the levels evaluated (0.925; 0.969 and 1.045 kg day-1, respectively). Stocking rate and live weight gain per hectare showed a linear relation with nitrogen levels. The efficiency of animal production was 2.040 and 1.766 kg of weight gain per kg of nitrogen used for the dose of 150 and 300 of N, respectively. The stocking rate and live weight gain per hectare of beef calves increased with the nitrogen levels, from 0 to 300 kg of N ha-1. However, the best efficiency in weight gain per unit of nitrogen applied was obtained with the dose of 150 kg of N ha-1.
Beef cattle production on black oats and italian ryegrass pasture under nitrogen fertilization
Keywords: Calves; Nitrogen efficiency; Pasture; Weight gain